Thermal Degradation of Biodegradable Poly(butylene adipate-co-terephthalate)/Starch Blends - Chiangga, Surasak; Suwannasopon, Satayu; Trivijitkasem, Nutnarun (Supreya) (Agriculture and Natural Resources, 2012)
Thermal degradation of biodegradable poly(butylene adipate-co-terephthalate) /starch (PBAT/S) blends of 15 µm thickness was investigated by thermogravimetric analysis in a nitrogen atmosphere and in an air atmosphere at a flow rate of 20 mL.min-1. The non-isothermal experiments were conducted at five constant heating rates (β = 1, 2, 5, 10 and 15 oC.min-1) from 100 to 800 oC. The thermogravimetric curves showed two degradation stages in a nitrogen atmosphere and three degradation stages in an air atmosphere. The second stage occurred at temperatures from 366 to 418 and 369 to 421 oC respectively. Three models—namely, the model-free isoconversion methods of Kissinger-Akahira-Sunose (KAS), Ozawa-Flynn-Wall (OFW) and Friedman (FR) were used to determine the dependence of the apparent activation energy Eα. The results showed higher Eα values on conversion α in the nitrogen atmosphere. The average Eα levels were 172, 174 and 173 kJ.mol-1 in the nitrogen atmosphere and 159, 159 and 160 kJ. mol-1 in the air atmosphere for the KAS, OFW and FR methods, respectively. This confirmed that thermal degradation in an air atmosphere is faster than in a nitrogen atmosphere.